Some Biological Observations on Short-Horned Grasshoppers (Orthoptera : Acridoidea) at Jodhpur, India - Parihar, D R (Annals of Arid Zone, 2016)
Notes are given on the biology of twelve species of short-horned grasshoppers very common in Indian desert. Number of generations per year were noted. Two species, viz., Oedaleus senegaensis and Sphingonotlls rubescens showed egg diapause. Sex-ratios of these species have been determined. Gravid females preferred sparsely distributed short grasses for oviposition and breeding. Seasonal changes in colouration of some species have been observed.